2002
DOI: 10.1063/1.1500731
|View full text |Cite
|
Sign up to set email alerts
|

Full-dimensional quantum wave packet study of rotationally inelastic transitions in H2+H2 collision

Abstract: We report full-dimensional accurate quantum dynamical calculations of the rotationally inelastic collision: para-H 2 ( 1 ϭ0,j 1 ϭ0)ϩpara-H 2 ( 2 ϭ0,j 2 ϭ0)→para-H 2 ( 1 ϭ0,j 1 Ј)ϩpara-H 2 ( 2 ϭ0,j 2 Ј), using a wave packet approach based on the Chebyshev polynomial expansion of Green's operator. The six-dimensional Hamiltonian within the coupled-states approximation is discretized in a mixed grid/basis representation and its action is computed in appropriate representations facilitated by a series of one-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Another area of interest in the study of the H 4 system are the calculation of nonreactive vibrational de-excitation cross sections using full-dimensional QM methods of both time-independent [46][47][48][49] and time-dependent type. 50,51 Recently, we performed full-dimensional time-dependent wave packet calculations of the H 2 + D 2 reaction and its isotopic variants on the ASP and BMKP PESs with J = 0. 52 The role of both vibrationally and rotationally excited reagents was examined.…”
Section: Introductionmentioning
confidence: 99%
“…Another area of interest in the study of the H 4 system are the calculation of nonreactive vibrational de-excitation cross sections using full-dimensional QM methods of both time-independent [46][47][48][49] and time-dependent type. 50,51 Recently, we performed full-dimensional time-dependent wave packet calculations of the H 2 + D 2 reaction and its isotopic variants on the ASP and BMKP PESs with J = 0. 52 The role of both vibrationally and rotationally excited reagents was examined.…”
Section: Introductionmentioning
confidence: 99%
“…13,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Quantum calculations are the primary source of state-resolved rate coefficients for astrophysical modeling. Excitation of rotational and vibrational levels of H 2 by collisions with H, H + , He, H 2 , and electrons followed by emission of quadrupole radiation is considered to be the main cooling mechanism of the primordial gas.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many of the early H 2 -H 2 calculations resorted to the rigid-rotor approximation. However, in the last several years, a number of full-dimensional quantum calculations have been reported within the timedependent 45,47,[49][50][51][52] and time-independent 13, 44, 46, 53-55 quantum formalisms. Some of these calculations have adopted the coupled-states approximation, [44][45][46][47] which was shown to be reliable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These PESs have been used in several different calculations. [32][33][34][35][36] However, in our previous works 12,34 we found that in the case of low energy H 2 +H 2 collision these PESs provide different results for some specific state-resolved cross sections. The difference may be up to an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%